2005
DOI: 10.1085/jgp.200409130
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis in the Voltage Dependence of HCN Channels

Abstract: Hyperpolarization-activated, cyclic nucleotide-gated (HCN) ion channels are important for rhythmic activity in the brain and in the heart. In this study, using ionic and gating current measurements, we show that cloned spHCN channels undergo a hysteresis in their voltage dependence during normal gating. For example, both the gating charge versus voltage curve, Q(V), and the conductance versus voltage curve, G(V), are shifted by about +60 mV when measured from a hyperpolarized holding potential compared with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
105
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 42 publications
10
105
3
Order By: Relevance
“…It also markedly accelerated the activation time course of I h (from τ act-40mV = 386.9 ± 52.6 ms to τ act-40mV = 282 ± 31.1 ms, n = 10, p < 0.05, paired t test). This is consistent with a voltage dependent hysteresis as described for certain HCN channels [11]. The holding currents remained comparable ( I holdini = 52.9 ± 12.4 pA. vs .…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…It also markedly accelerated the activation time course of I h (from τ act-40mV = 386.9 ± 52.6 ms to τ act-40mV = 282 ± 31.1 ms, n = 10, p < 0.05, paired t test). This is consistent with a voltage dependent hysteresis as described for certain HCN channels [11]. The holding currents remained comparable ( I holdini = 52.9 ± 12.4 pA. vs .…”
Section: Resultssupporting
confidence: 89%
“…Consistent with that model, activating mouse HCN1 channels facilitates I h by depolarizing its voltage dependence as revealed in intact frog oocytes (by recordings in 2 electrode voltage clamp) [11]. This depolarizing shift might be pronounced under certain conditions (up to +60 mV) preventing arrhythmic firing in model cells of sino-atrial node [11]. We previously found that in intact mammalian cells (HEK293) (by recordings in cell-attached mode) strong hyperpolarizations led to a reduction of maximum rat (r)HCN1 mediated I h [12].…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10][11] A fascinating feature of ion channels is their bistable behavior reflected in the hysteretic conductance under time-varying voltage showing physiologically functional bio-molecular memory. [12][13][14][15][16] Theoretical analyses have shown that comparable time scales of the external perturbation and system's natural relaxation give rise to such kind of behavior in model systems 17 as well as in ion channels. 18,19 Recently, nonequilibrium response spectroscopic technique 20,21 with periodic voltage protocol is used to study the ion channel kinetics in out-of-equilibrium situations.…”
Section: Introductionmentioning
confidence: 99%